Penguatan Peran Perguruan Tinggi Islam Dalam Mendorong Pengembangan Lembaga Keuangan Syariah di Indonesia - Murtiadi Awaluddin (Jurnal Iqtisaduna, 2018)
The purpose of this study is to formulate appropriate strategies in strengthening the role of Islamic universities in encouraging the development of Islamic financial institutions in Indonesia. Researchers took the object of research on three PTKI in Makassar.  The type of research is qualitative analysis of phenomological approach. Data is obtained from primary data in the form of statements and attitudes, then secondary data in the form of relevant literature and support the discussion of research, documentation. Techniques of collecting data in the form of observation, documentation, interview (Interview) directly with the parties concerned. Then the technique of processing and data analysis is done through four stages, namely: data collection, data reduction, data presentation, and conclusion. The result shows that Islamic University has great potential and role in supporting the development of Shariah financial institutions in Indonesia both in terms of human resource needs, as well as the marketing potential of syariah financial products.